Lichens across land use types of Mt. Musuan, Bukidnon, Southern Philippines - Taer, Ermalene C (Philippine Journal of Science, 2023)
Explorations on the knowledge and biodiversity of Philippine lichen fungi have progressed recently. However, comparatively little attention has been given to the species composition along a lowland secondary forest ecosystem. Thus, the study aimed to provide information on the occurrence of lichen species in relation to various land use types of Mt. Musuan of Mindanao Island, surrounded by forest fragments and cultivated agricultural areas. A series of transect walks and opportunistic sampling revealed a total of 38 lichen species distributed in 26 genera and 14 families. Among the land use types, the mixed species forest harbors the highest recorded species with 22, followed by teak forest and built-up (peak/summit) with 15 and 14 species, respectively. Lichens with the most represented families were revealed to be Graphidaceae with 10 species; Caliciaceae with six species; Physciaceae, Parmeliaceae, and Arthoniaceae with three species each; and Pyrenulaceae, Collemataceae, Letrouitiaceae, and Trypetheliaceae with two species each. Out of these collections, two species – viz. Letrouitia subvulpina (Nyl.) Hafellner and Pyrenula globifera (Eschw.) Aptroot – were new records in the Philippines. The results of this study will provide information to encourage effective management and biodiversity conservation efforts of various land use types, as lichens are sensitive to anthropogenic threats and pressures from environmental conditions.